Parental social support affects the learning responsibilities of elementary school students - Annisa Firdausi Nuzula; Supriyadi Supriyadi (Indonesian Journal of Islamic Studies, 2022)
The study aims to determine whether there is a relationship and how big the relationship is. Non-experimental quantitative research with a population of 53 students. Questionnaire instrument on learning responsibilities and parental social support. Test the validity of expert judgment, reliability test using the Alpha Conbach formula. Data analysis using Product Moment correlation. The results of the study the reliability value of learning responsibility was 0.975, and parental social support was 0.954. The results of the analysis of learning responsibilities show the medium category the results are 64%. and parental social support is in the moderate category, the result is 66%. significance 0.000≤0.05, Ho is rejected and Ha is accepted and the results of the correlation test rcount 0.549. The conclusion is that there is a relationship between learning responsibility and the social support of parents of SD Negeri 1 (Se-cluster) 1 Solokuro students.